Survival, Incidence, and Mortality Trends in Female Cancers in the Nordic Countries - Filip Tichanek; Asta Försti; Otto Hemminki; Akseli Hemminki; Kari Hemminki (Hindawi Limited, 2023)
Background. Female cancers cover common breast cancers, relatively common endometrial, ovarian, and cervical cancers and rare vulvar cancer. Survival in these cancers is known to be relatively good compared to all cancers but long-term studies for these cancers are rare, and to fill the gap, here, we generate survival data through 50 years. Materials and Methods. We applied generalized additive models to data from the NORDCAN database and analyzed 1- and 5-year relative survival for these cancers in Denmark (DK), Finland (FI), Norway (NO), and Sweden (SE) over half a century (1971-2020). Conditional 5/1-year survival for patients who survived the 1st year after diagnosis and annual survival changes was also estimated. Results. In 2016-20, 5-year survival was best for breast cancer reaching 92.3% (in SE), followed by endometrial cancer at 86.1% (SE) and cervical cancer at 75.6% (NO). Improvement in 5-year survival over the 50 years was the largest for ovarian cancer (20% units), finally reaching 52.9% (SE). For vulvar cancer, the final survival was between 70 and 73%. The best 5-year survival rate in 2016-20 was recorded for SE in breast, endometrial, and ovarian cancers; NO showed the highest rate for cervical and DK for vulvar cancers. DK had the lowest survival for breast and ovarian cancers, and FI, for the other cancers. Conclusions. The overall survival development appeared to consist of continuous improvements, most likely because of novel treatment and imaging techniques as well as overall organization of patient care. The large survival improvement for ovarian cancer was probably achieved by a surgical focus on tumors spread in the peritoneal cavity. For cervical and vulvar cancers, the high early mortality requires attention and could be helped by raising increasing public awareness of early symptoms in these cancers and developing pathways for fast initiation of treatment.